Radular Morphology and Relationship Between Shell Size and Radula Size of Few Dominating Intertidal Gastropod Mollusks of Veraval Coast, Gujarat - Gajera, Niyati; Vakani, Bhavik; Kundu, Rahul (Frontiers in Marine Science, 2022)
The radula is the main feeding organ and also very significant to majority of the Molluscs (especially Gastropod) taxonomy. With shell morphology, radular morphology are the key characters for the identification of gastropods species. The shape and structure of the radular teeth are unique to family to species level. In this study, five basic type of radula (docoglossan, rhipidoglossan, taenioglaossan, stenoglossan and taxoglossan) were observed from total of 23 different species belonging to 12 families were examined. Collection of the voucher intertidal gastropod specimen for study had initiated during May to October 2019 in rocky intertidal area near Veraval of the south Saurashtra coastline. Direct handpicking methods were used for collection of the specimen for experiments.